Internationalization strategy of Chinese private enterprises in Europe : Shuguang-learn by doing - Yang, Shengyun; Yue, Tao (London : Rotterdam School of Management, Erasmus University, 2012)
The Chinese firm "Nanjing Shuguang Chemical Group Co., Ltd" a leading chemical company in china was facing tough times operating in the European market due to various socio economic factors until it entered the Dutch market thanks to the economic connection between China and the Netherlands. The Netherlands is currently ranked the third largest investor in China within European countries. China is focusing on the Dutch market specifically because it is a single point of entry into Europe and its geographical location is suitable for logistics, which will save Chinese firms time and money. Additionally, the investment market is appealing to Chinese firms for its high quality of infrastructure, lower operating costs and ease of doing business and last, the tax structure of the country is attracting Chinese firms due to low tax rates, VAT and corporate tax.
Originally Published InYang, S., & Yue, T. (2012). Internationalization Strategy of Chinese Private Enterprises in Europe: Shuguang-Learn by Doing. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; China -- Foreign economic relations -- Netherlands; Netherlands -- Foreign economic relations -- China